As mulheres maravilha brasileiras vão à sala de aula: história, lutas e conquistas dos direitos das mulheres no Brasil - Martins, Joana Adriana Nunes (2018)
This thesis is the result of readings and researches based on the experience of the researcher as a woman and educator of basic education in the outskirts public school network in the state of Rio Grande do Sul. It aims to provide visibility to the Brazilian women’s protagonism in the history of the country; it also intended, by the problematization and observation of the educational practices that emerge in the daily life of schools – within the perspective of gender and feminism – to give voice to women. For that, I sought to rescue the biographies of Brazilian women who fought for rights and, with their achievements, were fundamental for understanding our historical moment. I reflect on the invisibility of women in History textbooks, as well as the role of history teaching in the formation of subjects’ subjectivities. On the other hand, I try to conjecture about conservative attempts to silence educators and the project that aims to silence our voices, imposing a political-military-religious ideology. In order to instrumentalize the teachers, I bring as a final production a timeline of the History of Women’s Rights in Brazil, together with ten cards with biographies of ten “Brazilian Wonder Women” and a notebook with suggestions for activities. Therefore, this work intends to provide visibility to women, strengthen and encourage discussion about gender, feminism and female protagonism. Thus, it wants to favor the effective, critical, autonomous and creative participation of both girls and boys, for a more human society, and with more equality and equity among people.